Impact of Frailty and Comorbidities on Surgical Outcomes and Complications in Adult Spinal Disorders. Issue 18 (15th September 2018) - Yagi, Mitsuru; Fujita, Nobuyuki; Okada, Eijiro; Tsuji, Osahiko; Nagoshi, Narihito; Tsuji, Takashi; Asazuma, Takashi; Nakamura, Masaya; Matsumoto, Morio; Watanabe, Kota
Abstract : Study Design: Retrospective review of surgically treated 481 adult patients with spinal disorders. Objective: The aim of this study was to elucidate the effect of frailty and comorbidities on postoperative health-related quality of life (HRQoL) and complication rates. Summary of Background Data: Elective surgeries for spinal disorders not only improve clinical outcomes but also have high complication rates. Methods: We retrospectively reviewed the results of consecutive elective spine surgeries for 156 adult spinal deformities (ASDs: 65 ± 9 years), 152 degenerative spondylolisthesis (DS: 64 ± 10 years), or 173 lumbar spinal canal stenosis (LSCS: 71 ± 9 years) with follow-up of at least 2 years. Modified Frailty Index (mFI) and Charlson Comorbidity Index (CCI) were determined from baseline demographics. We compared the prevalence and the influence of mFI and CCI on postoperative outcomes and complication rates. Results: The mFI and CCI were significantly worse in ASD than in others (mFI: ASD 0.09 ± 0.12, DS 0.06 ± 0.06, LSCS 0.04 ± 0.05, P  < 0.01. CCI: ASD 2.1 ± 1.6, DS 1.4 ± 0.7, LSCS 1.6 ± 0.9, P  < 0.01). Postoperative HRQoL deteriorated as mFI worsened in ASD (nofrail: Oswestry Disability Index [ODI] 26 ± 11, Scoliosis Research Society Questionnaire [SRS] 3.7 ± 0.7; prefrail: ODI 32 ± 12, SRS 3.6 ± 0.6; frail: ODI 42 ± 15, SRS 3.2 ± 0.7). In DS and LSCS, however, SF-36 physical component score and mental component score improved regardless of mFI and CCI. The 2-year major complications rate increased with frailty (36%, 58%, and 81%) in ASD, but not in others. Conclusion: ASDs were more frail and had more comorbidities than the other populations. In ASD, postsurgical outcomes and complication rates deteriorated as frailty and CCI increased, whereas surgery produced favorable outcomes and acceptable complication rates in DS and LSCS regardless of frailty and CCI. Careful patient selection and treatment of comorbidities before surgery may decrease complications and improve outcomes for the surgical treatment of ASD. Level of Evidence: 4 Abstract : Supplemental Digital Content is available in the text